Peranan GCG Dan Struktur Kepemilikan Dalam Meminimalisir Biaya Keagenan Pada Perusahaan Manufaktur Di BEI - Andrew Gunawan (Politeknik Ganesha Medan, 2022)
Agency costs are a problem for most companies, especially for manufacturing companies. Indeed, agency costs arising from deviant management practices can be minimized with good corporate governance or what is known as good corporate governance. One form of good governance is the existence of an independent board of commissioners that functions as a supervisory mechanism in the company. In addition, the ownership structure also has its own role to overcome this problem. This study aims to see how the role of good corporate governance and ownership structure in minimizing agency costs in a company. The method used in this study is multiple linear regression analysis, the result is the proportion of independent commissioners and institutional ownership has no significant effect on agency costs.